Evolution of facial innervation in anomodont therapsids (Synapsida): Insights from X‐ray computerized microtomography. (21st February 2018) - Benoit, Julien; Angielczyk, Kenneth D.; Miyamae, Juri A.; Manger, Paul; Fernandez, Vincent; Rubidge, Bruce
Abstract: Anomodontia was the most successful herbivorous clade of the mammalian stem lineage (non‐mammalian synapsids) during the late Permian and Early Triassic. Among anomodonts, Dicynodontia stands apart because of the presence of an osseous beak that shows evidence of the insertion of a cornified sheath, the ramphotheca. In this study, fourteen anomodont specimens were microCT‐scanned and their trigeminal canals reconstructed digitally to understand the origin and evolution of trigeminal nerve innervation of the ramphotheca. We show that the pattern of innervation of the anomodont "beak" is more similar to that in chelonians (the nasopalatine branch is enlarged and innervates the premaxillary part of the ramphotheca) than in birds (where the nasopalatine and maxillary branches play minor roles). The nasopalatine branch is noticeably enlarged in the beak‐less basal anomodont Patranomodon, suggesting that this could be an anomodont or chainosaur synapomorphy. Our analyses suggest that the presence or absence of tusks and postcanine teeth are often accompanied by corresponding variations of the rami innervating the caniniform process and the alveolar region, respectively. The degree of ossification of the canal for the nasal ramus of the ophthalmic branch also appears to correlate with the presence of a nasal boss. The nasopalatine canal is absent from the premaxilla in the Bidentalia as they uniquely show a large plexus formed by the internal nasal branch of the maxillary canal instead. The elongated shape of this plexus in Lystrosaurus supports the hypothesis that the rostrum evolved as an elongation of the subnarial region of the snout. Finally, the atrophied and variable aspect of the trigeminal canals in Myosaurus supports the hypothesis that this genus had a reduced upper ramphotheca. Abstract : The evolution of the trigeminal nerve in Anomodontia is used to unfold the evolutionary history of beak innervation in this group. It highlights a highly homoplastic evolution that varies with the dentition, cranial morphology, and phylogeny.